Numerical Investigation on Convective Heat Transfer of Infants and Adults under Ventilation (Journal of Fiber Bioengineering and Informatics, 2024)
There is a severe lack of research on the heat transfer mechanisms for various populations, with moststudies primarily concentrating on adults. This study aimed to investigate the difference in the convectiveheat transfer coefficient (${\rm h}_c$) of the whole and individual body parts between infant and adult underventilation. A numerical model for heat transfer between the human body and the environment wasdeveloped and validated against experiments involving a baby thermal manikin. The temperature andairflow fields surrounding the human body and the value of ${\rm h}_c$ were simulated under seven air velocitiesranging from 0.1 m/s to 2.5 m/s. The results indicated that, under natural ventilation, the overall ${\rm h}_c$ for infants and adults was 4.82 W/${\rm m}^2$·K and 4.29 W/${\rm m}^2$·K, respectively. Infants exhibited higherregional ${\rm h}_c$ values at their surface than adults, especially on their hands and feet. This discrepancy wasmore pronounced as the air velocity increased. Furthermore, regression equations were developed for thetwo body sizes to establish the connection between ${\rm h}_c$ and air velocity. These findings contribute to abetter understanding of the complex interplay between body size and convective heat transfer, providingfundamental data for enhancing the accuracy of infant thermal response predictions by incorporatingmore precise boundary conditions.
Keywords: Convective Heat Transfer Coefficient; Numerical Simulation; Body Size; Infant; Air Velocity.